Pemanfaatan Teknologi Sistem Pirolisis Skala Kecil Menggunakan Kompor Oli Bekas sebagai Pemanas - Sutrisno, Sutrisno; Romero , Rendyka Dwi; Dewi, Elsa Sintya; Putri, Jeesica Diana; Fauzan , Alfi Syahri; Ardiatma, Dodit (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The rapid development of technology, particularly Artificial Intelligence (AI), has significantly influenced educational practices, including English language learning. This study aimed to investigate the implementation of Artificial Intelligence in English language learning and explore eighth-grade students’ perceptions toward the use of AI at SMPK 1 Harapan Denpasar. This study employed a descriptive qualitative research design involving 36 eighth-grade students, with seven students selected as interview participants through convenience sampling techniques. Data were collected through observation, questionnaires, interviews, and document analysis. The collected data were analyzed using the interactive model proposed by Miles et al., including data reduction, data display, and drawing conclusions. The findings revealed that AI had been successfully integrated into English learning activities and contributed positively to classroom learning processes. The implementation of AI created a more interactive learning environment and increased students’ enthusiasm and engagement during learning activities. Furthermore, students demonstrated highly positive perceptions regarding the use of AI based on the Technology Acceptance Model (TAM) indicators, namely perceived usefulness and perceived ease of use. Students perceived AI as beneficial in supporting vocabulary development, grammar improvement, pronunciation practice, and assignment completion. AI was also considered easy to use because it provided quick responses and accessible features that encouraged independent learning. Although students recognized certain limitations such as inaccurate responses and system errors, they demonstrated critical awareness by evaluating and verifying AI-generated information. Therefore, the findings suggest that Artificial Intelligence has considerable potential to support and improve the effectiveness of English language learning.